Carbon Monoxide (CO), Nitric Oxide, and Hydrogen Sulfide Signaling During Acute CO Poisoning - Coburn, Ronald F. (Frontiers in Pharmacology, 2022)
45 Major toxic effects of acute carbon monoxide (CO) poisoning result from increases in reactive 46 oxygen species and reactive nitrogen species (RNS) producing oxidative stress. The importance 47 of altered nitric oxide (NO) signaling in evoking increases in RNS during CO poisoning has been 48 established. Although there is an extensive literature describing NO and hydrogen sulfide (H2S) 49 signaling in different types of cells under normal conditions, how CO poisoning-evoked 50 deregulation of additional NO signaling pathways, and H2S signaling pathways, could result in 51 cell injury has not been previously considered in detail. The goal of this article was to do this. 52 The approach was to use published data to describe signaling pathways driven by CO bonding to 53 different hemoproteins. Then to collate data that emphasize NO and H2S signaling pathways that 54 could interact with CO signaling pathways and be important during CO poisoning. Arteriolar 55 smooth muscle cells-endothelial cells located in the coronary and some cerebral circulations 56 were used as a model to illustrate major signaling pathways driven by CO bonding to different 57 hemoproteins. Results support a hypothesis that multiple deregulated and interacting NO and 58 H2S signaling pathways can be involved in producing cell injury evoked during